2020
DOI: 10.1111/ssqu.12832
|View full text |Cite
|
Sign up to set email alerts
|

Does Compulsory Schooling Affect Innovation? Evidence from the United States

Abstract: Objective U.S. states adopted compulsory schooling laws between 1852 and 1929. This is the first study to empirically test the historical relationship between the adoption of state‐level compulsory schooling laws and measures of innovation and entrepreneurship such as the number of patents per capita and output per worker. Methods We use difference‐in‐difference and event study methods to estimate the effects of these laws. Results Our results suggest that the adoption of compulsory schooling in the United Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Eq. (16) The relationship between the endogenous observed variables and the endogenous structural variables is the factor loading matrix of the endogenous observed variables on the endogenous structural variables.…”
Section: ( )mentioning
confidence: 99%
See 1 more Smart Citation
“…Eq. (16) The relationship between the endogenous observed variables and the endogenous structural variables is the factor loading matrix of the endogenous observed variables on the endogenous structural variables.…”
Section: ( )mentioning
confidence: 99%
“…Literature [15] analyzed students' preferences for each stage of innovation and entrepreneurship based on the Moore-Bygrave Entrepreneurship Laddering Framework, and these insights and takeaways can help to tailor innovation and entrepreneurship education to students in different situations in order to increase students' overall innovation and entrepreneurship education interest and ability. Literature [16] conducted an in-depth examination and investigation of how compulsory education affects students' innovation and entrepreneurship preferences and concluded that compulsory education inhibits students' ability to innovate and their curiosity to explore the world.…”
Section: Introductionmentioning
confidence: 99%
“…Innovation is not a sensation of modern society, rather it walks together with and sometimes leads the human civilization since its primitive era. Innovation brings changes in human behavior, the ratio of production factors, and life use (DeAngelis and Dills 2020; Jeong and Alhanaee 2020; Staples 2020). Innovation produces new ideas and enriched production means making the goods viable and more marketable.…”
Section: Figurementioning
confidence: 99%
“…The Implementation Opinions on Deepening the Reform of Innovation and Entrepreneurship Education in Colleges and Universities issued by the General Office of the State Council in 2015 mark that the country has taken Innovation and entrepreneurship education as a core strategy [1][2][3]. As an important base for talent cultivation and a power source for social Innovation and development, colleges and universities play an important role in building an innovative country [4][5]. As the goal of Innovation and entrepreneurship education, colleges and universities must follow the trend, correctly position themselves, effectively adjust, and make due contributions to the realization of the new goal, and further promote the national strategy of developing the country through science and education and the strategy of strengthening the country through talents [6][7].…”
Section: Introductionmentioning
confidence: 99%